Investigation of the production and mechanical properties of porous Beta Titanium alloy compacts prepared by powder metallurgy processes for biomedical applications - Nugroho, Aris Widyo (Curtin University, 2013)
Titanium and its alloys are known to be widely used for biomedical applications due to their biocompatibility, and excellent corrosion resistance. The introduction of porosity into the metals may reduce the stiffness to match that of bone and allow the completion of bone ingrowth into the porosity of the implant leading to improvement in implant fixation. Porous metals are recognised in demonstrating considerable advantages in a wide variety of applications due to their low density and novel physical, mechanical, thermal, electrical and acoustic properties. These materials have already exhibited potential for lightweight structures, thermal management, energy absorption and more recently for biomedical applications.The present study was carried out to develop porous titanium alloys from elemental powders, i.e. titanium, niobium, tantalum and zirconium using a powder metallurgy method based on the argon filled pore expansion technique. This technique utilises highly pressurised argon pores created by the hot isostatic pressing of metal powders, in the presence of argon gas followed by expansion of the pressurised argon at high temperature. The objectives of the research are : (i) to investigate a novel procedure on developing porous beta (titanium alloys from elemental powders (titanium, niobium, tantalum and zirconium) based on the expansion of the pressurised argon bubble technique, (ii) to determine the effect of foaming parameters on the microstructure, phase transformation and resulting porosity of the porous alloys, (iii) to determine the compressive elastic modulus and compressive strength of the porous alloy.The powder form of starting materials, i.e. titanium, niobium, tantalum and zirconium in angular shape with the size and purity of the elemental powders being <44μm and >99.5%, respectively, were weighed to attain a nominal composition of Ti-29Nb-13Ta-4.5Zr, and were then blended in a roller mixer. Following this, the blended powder was placed into stainless steel cans. Each can was subsequently evacuated and then backfilled with 0.34, 0.48, 0.68 and 0.86 MPa of argon gas and sealed. Afterwards, the pressurised cans were hot isostatic pressed (HIP-ed) at 1100oC under 100 MPa of argon pressure for 4 hours followed by furnace cooling. Cubic specimens each of approximate nominal dimensions of 10 x 10 x 10 mm were sectioned from the HIP-ed billet using wire electrical discharge machining (WEDM). The cube specimens were then foamed in an argon flushed graphite element vacuum furnace at 1100o, 1225o and 1350oC for 10 hours.Following this, the foamed specimens were prepared for microstructural analysis and examined using optical microscopy and scanning electron microscopy. The fraction of porosity was determined using digital image analysis using open source software (ImageJ). Phase identification within the specimens was carried out using X-ray diffraction (XRD) and/or Synchrotron Radiation Diffraction (SRD). Hardness values were obtained by using a microvickers hardness tester. Open-circuit potential (OCP) and potentiodynamic polarisation measurements were performed to evaluate their corrosion behaviour. Compression tests were carried out using standard mechanical testing equipment, in which the specimen strain was measured using two clip gauges attached to the platen surfaces in contact with the specimen.The experimental results are summarised as follows. A novel procedure using elemental powders in the argon filled pore expansion technique to produce porous β titanium alloy has been developed. Hardness, corrosion potential (Ecorr) and corrosion current density (icorr) values of the developed titanium alloy were in the range of 340–474 HV, 445 mV to -321 mV and 0.322 A/cm2 to 1.51 A/cm2 respectively which is comparable to those of Ti-6Al-4V or commercially pure (CP) Ti. Regarding the porous structure, although the resulting porosities are comparable with that obtained using existing techniques, the elastic modulus was found to be lower and the compressive strength slightly lower than that of alpha-beta (α+β) titanium alloys. The porosity level was found to reach approximately 17.8% at a temperature of 1100oC for 20 hours.Foaming at higher temperatures resulted in the development of α phase. At 1225oC the αphase areas became larger and at 1350oC the α phase continued to grow by forming α platelets within the β phase matrix. Pore morphology of the samples foamed at 1225oC remained discrete with few coalesced pores and a porosity level of 37.1% was achieved. Foaming at 1350oC resulted in the pores growing considerably larger with multiple pores sometimes having become interconnected with porosity levels and pore size reaching approximately 40.2% and 200 μm, respectively. The elastic modulus and compressive yield strengths of the three sets of foamed samples were all found to decrease with the increase of porosity.However, an increase in modulus and yield strength was the trend with increasing foaming temperature. The experimental results indicate that porous β βtitanium alloys can be produced using elemental powders in the argon filled pore expansion technique, and these materials exhibit properties inclusive of those required for biomedical applications.